Jejak Pemikiran Strategik pada Pembangunan Jalan Tol Trans Jawa dan Trans Sumatera - Lukas Oktavianus Maruli Manalu; Mugi Harsono (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2023)
The purpose of this research is to elaborate on the strategic thinking behind the construction of the Trans Java (JTTJ) and TransSumatra (JTTS) Toll Roads, and the multiplier effect that will be generated in the future. This paper is also expected to encourage decision-makers to develop ideas that can produce strategic decisions that affect the organization’s long-term performance. For example, the decision to build JTTS and JTTJ is estimated that this will organization’s long-term performance. This construction will trigger new industrial areas, and the availability of many varied jobs so that the workforce with higher education can be distributed. It is hoped that this will also have an impact on increasing Gross Domestic Product (GDP), growth, and economic equity so that Indonesia can leave the regional imbalance that has long been questioned. The development of JTTS and JTTW is not a reflection of the courage of leaders to take risks amid scarce financial resources but shows the ability to think strategically in choosing the right leverage to increase growth and economic equity, all at once.